The State Of Quality Of Teaching And Learning In Higher Education in South Africa: The Misalignments - Nkarhi Excellent Mathebula; Mohammed Xolile Ntshangase; Selina Ramapela; Ronnie R. Maceke (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
In the absence of adequate funding, the emphasis on enrolling a significant number of students in higher education sector often takes precedence over ensuring effective teaching and student achievement. Addressing persistent challenges such as improving academic outcomes, reducing university dropout rates, and maintaining access to quality higher education remains a critical concern in the sector. Even though admission to post-secondary education has increased, student success rates have not shown corresponding improvement. This qualitative study applied growth model theory to examine and evaluate the efficiency of tertiary education in South Africa. This research aimed to investigate the hurdles experienced by tertiary institutions in their efforts to produce graduates of high calibre. The research was guided by the question: How can misalignments within the education sector be addressed to enhance efficiency in higher education? The study sample comprised ten first-year undergraduate students. The research applied semi-structured interviews to gather evidence and thematic analysis was conducted to analyse data. In conclusion this study argues that in efforts to provide education to numerous previously disadvantaged groups, quality is often compromised in favour of quantity, creating an "articulation gap" Student unpreparedness represents a significant barrier to academic success, often resulting in high dropout rates or prolonged degree completion